Land Market Restrictions, Women's Labor Force Participation, and Wages in a Rural Economy - Emran, M. Shahe; Shilpi, Forhad (World Bank, Washington, DC, 2016)
This paper analyzes the effects of land market restrictions on the rural labor market outcomes for women. The existing literature emphasizes two mechanisms through which land restrictions can affect the economic outcomes: the collateral value of land, and (in) security of property rights. Analysis of this paper focuses on an alternative mechanism where land restrictions increase costs of migration out of villages. The testable prediction of collateral effect is that both wages and labor force participation move in the same direction, and insecurity of property rights reduces labor force participation and increases wages. In contrast, if land restrictions work primarily through higher migration costs, labor force participation increases, while wages decline. For identification, this paper exploits a natural experiment in Sri Lanka where historical malaria played a unique role in land policy. This paper provides robust evidence of a positive effect of land restrictions on womens labor force participation, but a negative effect on female wages. The empirical results thus contradict a collateral or insecure property rights effect, but support migration costs as the primary mechanism.